Social control in the rural community, a field study in the tribal norms in Al-Mahnawiya district (Journal of the College of Basic Education, 2022)
With the emergence of human gatherings and the multiplicity of forms of interaction between individuals and societies, the complexity of lifeSocial Individuals, social groups, and societies have begun to establish specific standards for regulating imagesMultiple social interactions and dealings, which have transformed over time from mere naive standards to othersThere are serious and binding standards that all members of society must abide by in their daily behaviorIn order to guarantee the rights of others and thus achieve a kind of social cohesion,